2021
DOI: 10.25122/jml-2020-0116
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ketamine on preventing postpartum depression

Abstract: Postpartum depression is a common disabling psychosocial disorder that could have adverse effects on the life of the mother, infant, and family. The present study was conducted to evaluate the effect of ketamine on preventing postpartum depression in women undergoing caesarian sections considering the relatively known positive effect of ketamine on major depression. The present double-blind, randomized clinical trial was conducted on 134 women undergoing scheduled caesarian sections. Participants were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
(20 reference statements)
1
20
0
Order By: Relevance
“…At 4 weeks postoperatively, the control group had a decrease in EPDS score to a mean of 13.09, which was a significant difference from the 2‐week postoperative mark, but not from the original EPDS mean scores. The intervention group had a decreased to a mean score of 10.84, which was significantly different from the preoperative scores, but not significantly different compared with the 2‐week scores for that group 45 . Essentially, although both groups showed significant improvements in depression scores at various times, the trending decrease happened at different points, warranting further study to examine why.…”
Section: Modern Psychedelic‐assisted Therapymentioning
confidence: 80%
See 1 more Smart Citation
“…At 4 weeks postoperatively, the control group had a decrease in EPDS score to a mean of 13.09, which was a significant difference from the 2‐week postoperative mark, but not from the original EPDS mean scores. The intervention group had a decreased to a mean score of 10.84, which was significantly different from the preoperative scores, but not significantly different compared with the 2‐week scores for that group 45 . Essentially, although both groups showed significant improvements in depression scores at various times, the trending decrease happened at different points, warranting further study to examine why.…”
Section: Modern Psychedelic‐assisted Therapymentioning
confidence: 80%
“…Women received either 1 to 2 mg/kg of sodium thiopental and 0.5 mg/kg of ketamine or just 3 to 5 mg/kg of sodium thiopental to induce anesthesia for their scheduled cesareans. 45 Depression scores between the intervention and control groups were not significantly different preoperatively. At 2 weeks postoperatively, the control group had an increase in the mean EPDS score to 14.34, although it was not significant, whereas the intervention group showed a significant decrease in the mean EPDS scores to 11.82 using a P value less than 0.001.…”
Section: Clinical Applications and Researchmentioning
confidence: 80%
“…Currently, there is no effective treatment to achieve the complete symptomatology remission of all PPD patients. Even though exogenous allopregnanolone (Brexanolone, Zulresso) has been recently approved as a unique treatment for PPD by the Food Drug Administration 19,20 and ketamine has been used as a prophylactic treatment after caesarean sections 22,58 , the exact mechanism of action of both drugs remains barely speculative. Here we demonstrated that low doses of ketamine reverse the depressive-and anhedonia-like behaviour induced by MSEW, as previously shown in other animal models of depression 59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, ketamine has also been suggested as promising drug for preventing PPD in women who undergo caesarian sections 22 . Ketamine is a glutamate N-methyl-d-aspartate (NMDA) non-competitive receptor antagonist that shows rapid antidepressant effects 23 .…”
Section: Introductionmentioning
confidence: 99%
“…A similar study by Alipoor et al ( 30 ) was conducted on 134 women undergoing c-section randomized to either ketamine (0.5 mg/kg) plus nesdonal (1–2 mg/kg) or nesdonal (3–5 mg/kg) alone administered intravenously during the induction phase of anesthesia. Participants were assessed with the EPDS at 2 and 4 weeks postpartum.…”
Section: Ketamine As a Prophylactic Agent For Postpartum Depressionmentioning
confidence: 99%